2017
DOI: 10.1530/erp-17-0052
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of subclinical myocardial dysfunction detected by two-dimensional and three-dimensional speckle tracking in asymptomatic type 1 diabetic patients: a long‑term follow-up study

Abstract: BackgroundWe sought to assess the long-term evolution of left ventricular (LV) function using two-dimensional (2D) and three-dimensional (3D) speckle tracking echocardiography (STE) for the detection of preclinical diabetic cardiomyopathy, in asymptomatic type 1 diabetic patients, over a 6-year follow-up.Design and methodsSixty-six asymptomatic type 1 diabetic patients with no cardiovascular risk factors were compared to 26 matched healthy controls. Conventional, 2D and 3D-STE were performed at baseline. A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 32 publications
0
29
1
7
Order By: Relevance
“…Moreover, Bjornstad et al found a significantly lower GCS with unaffected GLS in adolescent T1DM patients with a median disease duration of 4.6 years . This finding is in contrast to other studies proved that the impairment in longitudinal strain is one of the earliest signs of myocardial dysfunction in type 1 DM in due to the subendocardial damage caused by coronary microvascular ischemia …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, Bjornstad et al found a significantly lower GCS with unaffected GLS in adolescent T1DM patients with a median disease duration of 4.6 years . This finding is in contrast to other studies proved that the impairment in longitudinal strain is one of the earliest signs of myocardial dysfunction in type 1 DM in due to the subendocardial damage caused by coronary microvascular ischemia …”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, Ringle et al showed that only longitudinal strain by 2D STE has significantly reduced in adults with T1DM than healthy controls after 6 years of follow up, whereas circumferential strain was preserved . They suggested that longitudinal fibers are affected early in diabetic cardiomyopathy, whereas the circumferential function affected only in long durations exceeding 10 years or coexisting complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 3D‐LV AS was found to be lower in the prediabetic and diabetic patients than in the controls. Moreover, Ringle et al . and Ng et al .…”
Section: Discussionmentioning
confidence: 99%
“…showed that 2D longitudinal and radial functions of each LV segment were impaired in diabetic adult patients. Longitudinal strain impairment found to be one of the earliest sign of myocardial dysfunction in DM in several studies due to the effect of subendocardial damage caused by microvascular coronary ischemia …”
Section: Discussionmentioning
confidence: 99%